The role of chemokines and their receptors in cardiovascular diseases - Srikanth, Sashwath; DeVito, Louis; Constantinesco, Nicholas J.; Gopal, Radha (Frontiers in Immunology, 2026)
Cardiovascular diseases (CVD) are increasingly recognized as an outcome of multiple inflammatory processes. Despite a large recent research focus, the majority of attempts to therapeutically target chemokines, have not been successful. Thus, a better understanding of the mechanisms involving chemokines contributing to CVD is warranted to identify the missing gaps in the field. This review summarizes the latest developments on the role of chemokines in the pathogenesis of atherosclerosis, heart failure (HF), coronary artery disease, myocarditis, cardiomyopathy, and arrhythmias. We also aim to provide insight into the current clinical trials and potential therapeutics targeting chemokines and their receptors.